STUDY OF A COLLECTION OF SERVICE TIME DISTRIBUTIONS AND IMPACT IN THE RESPECTIVE M|G|? SYSTEM BUSY PERIOD PARAMETERS - Ferreira, M. A. M.; Filipe, J. A. (17th Conference on Applied Mathematics APLIMAT 2018, 2018)
The problems arising when computing the moments of a particular service time distributions collection, for which the M|G|? queue system busy period becomes very easy to study, are presented and it is shown how to overcome them. Some results, precisely about the moment’s computation of random variables with distribution functions given by this collection are given. The busy period “peakedness” and “modified peakedness” for the M|G|? queue in the case of those service time distributions are also computed.